Benefits from aerobic exercise in patients with major depression: a pilot study. Issue 2 (1st April 2001) - Dimeo, F; Bauer, M; Varahram, I; Proest, G; Halter, U
Abstract : Background —Several reports indicate that physical activity can reduce the severity of symptoms in depressed patients. Some data suggest that even a single exercise bout may result in a substantial mood improvement. Objective —To evaluate the short term effects of a training programme on patients with moderate to severe major depression. Methods —Twelve patients (mean (SD) age 49 (10) years; five men, seven women) with a major depressive episode according to the Diagnostic and Statistical Manual of the American Society of Psychiatry (DSM IV) criteria participated. The mean (SD) duration of the depressive episode was 35 (21) weeks (range 12–96). Training consisted of walking on a treadmill following an interval training pattern and was carried out for 30 minutes a day for 10 days. Results —At the end of the training programme, there was a clinically relevant and statistically significant reduction in depression scores (Hamilton Rating Scale for Depression: before, 19.5 (3.3); after, 13 (5.5); p = 0.002. Self assessed intensity of symptoms: before, 23.2 (7); after, 17.7 (8.1); p = 0.006. Values are mean (SD)). Subjective and objective changes in depression scores correlated strongly ( r = 0.66, p = 0.01). Conclusions —Aerobic exercise can produce substantial improvement in mood in patients with major depressive disorders in a short time.